Bullying dalam Perspektif QS. Al-Hujurat Ayat 11 dan Kolerasinya dengan Netizen di Media Sosial - Ayu, Putri; Zulfikar, Eko (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This article aims to discuss QS. al-Hujurat verse 11 and its correlation with bullying carried out by netizens on social media. The study was carried out using qualitative methods, library research and descriptive-analytical data analysis. The results and discussion of this study show that from several bullying problems emerging on social media, netizens who are involved in bullying behavior will harm individuals, regardless of the teachings contained in the QS. al-Hujurat verse 11. The author concludes that the negative impact of bullying on social media and its correlation with religious teachings through understanding QS. al-Hujurat verse 11, it is very important to create an online environment full of respect and empathy, in line with the values ​​of wisdom contained in the Qur’an. This article emphasizes the need for netizen awareness to contribute to creating a digital space that supports and respects diversity without creating pain and conflict between people. QS perspective. It is hoped that al-Hujurat verse 11 will be a basic guideline for netizens to be wise in using social media.